Alterations in the duodenum myenteric neurons of Wistar rats after ingesting of 2,4 dichlorophenoxyacetic acid - Pereira, J. N B; Scoz-Faglioni, J. R.; Germano, R. M.; Stabille, S. R.; Mari, R. B. [UNESP] (My University, 2013)
The 2,4 dichlorophenoxyacetic acid (2,4-D) is a systemic herbicide whose effects in animal organic systems have been examined in previous studies, being the neurotoxicity considered the predominant effect. However, the studies that detect the 2,4-D neurotoxicity have merely focused in the central nervous system, and therefore, little is known about the effect of this herbicide in the enteric nervous system. This study aimed to verifying the 2,4-D effects on the myenteric neurons in duodenum of Wistar rats. Ten 60-day-old male Wistar rats (Rattus norvegicus) were divided in two groups: control group (C) that did not receive 2,4-D and experimental group (E) that received 5.0 mg of 2,4-D/kg for 15 days. At the end of experimental period, the animal were euthanized, the duodenum was collected and processed for NADPH-diaphorase histochemical analysis in order to expose the nitrergic myenteric neurons (NADPH-dp). In the light microscopy analysis, the whole-mount preparation obtained from duodenum of each animal were image-captured in 120 and 40 fields, for quantitative and morphometric analyses of myenteric neurons, respectively. The neuronal density was not affected when comparing the two groups, but an increase (p > 0.05) of 8.5% was observed in the cell body area of neurons in the E group. In conclusion, the ingestion of 2,4-D at a dosage of 5.0 mg/kg body weight for 15 days does not change the neuronal density, but promotes the hypertrophy of NADPH-dp myenteric neurons in duodenum of the rats of this study.
Keywords: Herbicide; Myenteric plexus; Nitrergic neuron; Small intestine